A visible-light responsive metal–organic framework as an eco-friendly photocatalyst under ambient air at room temperature. Issue 19 (21st August 2020) - Liu, Yanhong; Lin, Chen; Li, Bowen; Wang, Jian; Wang, Man; Zhang, Na; Feng, Yue; Wu, Pengyan
Abstract : A 2′, 7′-dichlorofluorescein-based MOF as a reusable photocatalyst for the synthesis of 1, 3-oxathiolane-2-imines from styrenes and NH4 SCN by utilizing visible light and air as the eco-sustainable and cheapest reagents. Abstract : Metal–organic frameworks (MOFs) have recently emerged as a new class of photocatalysts. However, most of these systems suffer from poor visible-light utilization, high cost, and low activity, and photocatalytically active MOFs in the visible-light spectral region are still relatively rare. Herein, a simple and effective strategy was developed to immobilize 2′, 7′-dichlorofluorescein inside a porous metal–organic framework (MOF) for the first time. The MOF was applied as the first example of a visible-light responsive MOF-based catalyst for straightforward synthesis of 1, 3-oxathiolane-2-imines from styrenes and ammonium thiocyanate under ambient air at room temperature, exhibiting good reusability, and the product can be scaled up to the gram level. The catalytic mechanism was also discussed. The approach reported in this study could open a new avenue in developing novel porous functional materials for a broad scope of visible-light-driven applications.